Evaluation of oat genotypes for species-specific and cross-resistance to Fusarium species and the role of trichomes in susceptibility - Schurack, Selma; Rodemann, Charlotte; Oldach, Klaus; Beuch, Steffen; Brodführer, Sophie; von Tiedemann, Andreas; Herrmann, Matthias Heinrich (Frontiers in Plant Science, 2025)
IntroductionFusarium head blight (FHB), caused by various Fusarium species, poses a significant threat to oat grain quality and yield. The presence of multiple Fusarium species raises the question whether FHB resistance in oats can be broadly effective and species non-specific (cross-resistance), or whether it is rather species-specific. While several morphological and biochemical factors are known to influence FHB resistance, the role of hull trichomes in oat resistance remains unclear.MethodsIn this study, 25 oat genotypes were evaluated for resistance to Fusarium graminearum (FG), F. sporotrichioides (FS), and F. poae (FP) in multiple field trials across Germany. Infection severity was quantified using Fusarium species-specific qPCR. Microscopic analyses were conducted to characterize trichome size and density on the lemma and palea. Results and discussionSpecies-specific qPCR showed the highest fungal biomass for FP, followed by FS and FG. Variability due to environmental factors was very high, resulting in rather low heritabilities for FG (0.50) and FS (0.36), and no significant genotype effect for FP. A significant positive correlation was found between FP and FS infection, whereas FG infection was not correlated with either FP or FS. Trichome size and density showed significant genotype-specific variation with high heritability (0.97). FG biomass was positively correlated with trichome size and density, and FG hyphae were observed in close interaction with trichomes and stomata. Our results indicate the presence of partial cross-resistance for FS and FP in addition to mostly species-specific resistance and suggest a role for trichomes in susceptibility to FG. These findings provide important insights for the development of Fusarium-resistant oat varieties while underscoring the complexity of breeding for broad FHB resistance in oats.